Penguatan Organisasi Pecinta Alam (Green Campus) Melalui Diklatsar - Kahan Tony Hendrawan; Joan Rhobi; Muslimin (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
Organization is a process of identifying, forming, team working, defining and delegating authority, responsibility and establishing relationships with the aim of enabling people to work together effectively towards set goals. Strengthening the organization is one of the goals of forming members who have knowledge, skills and mentality in accordance with the vision and mission of Green Campus organization. Training is the first step to provide an in-depth understanding of the values, culture and basic skills needed by members of an organization. One of effective way to improve the quality and capacity of human resources in an organization is through basic education and basic training. In training, new members are trained to understand the roles, responsibilities, technical and non-technical skills that are relevant to the organization's goals. Thus training is not just technical training, but also a process of mental strengthening, emotional and intellectual strength of its members. Through this activity, it can make the members of organizations become competent, professional and have high integrity, so that they are able to face future challenges more prepared and confident. The method used in implementing this community service consists of three stages, namely: planning, implementing mentoring, and evaluating the results of mentoring. In this community service activity there were 10 participants. In this evaluation there are four aspects namely: (1) Usefulness, (2) Understandability, (3) Strengthening methods, and (4) Suitability. So, it can be concluded that this activity really hit the targets or participants as shown by the evaluation results with an average score is very good (86.20%), and good (13.80%).